La téléconsultation : un levier pour rehausser l’accès aux services de santé en français pour les communautés francophones en situation minoritaire de l’Ontario - Dorion, Michelle; Giroux, Isabelle; Dionne, Éric (Reflets, 2026)
Les écrits démontrent que l’accessibilité aux services de santé en français est lacunaire chez les communautés francophones vivant en situation minoritaire (CFSM). Cette barrière linguistique est alarmante, car elle peut avoir des conséquences graves sur la qualité des soins et sur la sécurité des patientes et patients francophones. Face à cette réalité, la téléconsultation représente une solution technologique prometteuse permettant d’élargir l’offre des services de santé en français pour les CFSM. Ainsi, cet article présente un point de vue critique quant à l’utilisation de la téléconsultation en abordant les avantages et les limites qui lui sont associés. Les possibilités qu’offre ce dispositif pour rehausser les services de santé en français chez les CFSM seront également abordées en tenant compte des données recueillies auprès de patientes et patients ainsi que des prestataires de soins de santé francophones concernant leurs expériences avec l’utilisation de la téléconsultation à l’Hôpital Montfort, un centre hospitalier francophone en Ontario. Research shows that access to healthcare services in French is deficient in Francophone minority communities. This language barrier is alarming as it can have negative impacts on the quality and safety of care provided for Francophone patients. Faced with this reality, teleconsultation is a promising technological solution to enhance the offer of services in French for Francophone minority communities. Thus, this article presents a critical view on the use of teleconsultation by addressing its associated benefits and limitations. The possibilities this technology offers to enhance health services in French to Francophones living in a linguistic minority community will also be addressed by taking into account the experience with teleconsultation of French-speaking patients and healthcare providers at Montfort Hospital, a Francophone community hospital in Ontario.

Differences in experiences with episodic virtual care based on language of comfort for healthcare services in New Brunswick, Canada - Gallant, François; Forgues, Éric; Moffitt, Julie; Lavergne, M Ruth (BMC Primary Care, 2026)

Understanding acceptability of digital health technologies among francophone-speaking communities across the world: a meta-ethnographic study - Gauthier-Beaupré, Amelie; Grosjean, Sylvie (Frontiers in Communication, 2023)
Introduction: Increasingly, people are turning toward digital health technologies to support their care management, communication with health professionals, and performing activities of daily living. Digital health technologies may be well implemented in clinical practices in several jurisdictions, but the influence of sociocultural factors may sometimes be neglected. To increase use and sustainability of these innovative solutions in health care, we need to understand acceptability among diverse groups of the population such as linguistically diverse populations. Francophone-speaking populations in Canada, for example, are known to endure challenges with income, health and difficulties associated with living in rural areas which impede on their likelihood to use digital health technologies. As part of the University of Ottawa International Francophonie Research Chair on Digital Health Technologies, this study aimed to understand the conditions that make digital health technologies acceptable among francophone-speaking communities. Methods: Using a meta-ethnography methodology, this study synthesizes international qualitative research on social acceptability of digital health technology among francophone-speaking communities. We focused on four types of digital health technologies: telemedicine, mobile technologies, wearable technologies, and robotic technologies. Using Noblit and Hare's 7 phase approach to conducting a meta-ethnography, we were able to get a comprehensive synthesis and understanding of the research landscape on the issue. Studies published between 2010 and 2020 were included and synthesized using NVivo, excel and a mind mapping technique. Results: Our coding revealed that factors of social acceptability for digital health technologies could be grouped into the following categories: care organization, self-care support, communication with care team, relational and technical risks, organizational factors, social and ethical values. Our paper discusses the themes evoked in each category and their relevance for the included digital health technologies. Discussion: In discussing the results, we present commonalities and differences in the social acceptability factors of the different digital health technologies. In addition, we demonstrate the importance of considering sociocultural diversity in the study of social acceptability for digital health technologies. Implications: The results of this study have implications for practitioners who are the instigators of digital health technology implementation with healthcare service users. By understanding factors of social acceptability among francophone-speaking communities, practitioners will be better suited to propose and support the implementation of technologies in ways that are suitable for these individuals. For policymakers, this knowledge could be used for developing policy actions based on consideration for diversity.

Le programme de télésanté de prévention des chutes Marche vers le Futur : développement et retombées d’une communauté de pratique franco-canadienne - O’Neil, Jennifer; Dionne, Nathalie; Cardinal, Dominique; Savard, Jacinthe (Minorités linguistiques et société / Linguistic Minorities and Society, 2025)
Résumé Le programme de télésanté Marche Vers le Futur (MVF) a eu un impact positif sur le bien-être des personnes âgées francophones et sur leur accès aux services de prévention des chutes au Canada. L’objectif de ce projet était de développer et de mettre en place une communauté de pratique (CdP) facilitant le partenariat et le partage des connaissances entre les animateurs du programme MVF. La création de cette CdP a permis à vingt-deux animateurs de cinq provinces de partager des stratégies de recrutement, de promotion du programme et de sensibilisation quant aux besoins des personnes âgées francophones au pays. Quatre rencontres virtuelles ont permis d’identifier les obstacles à la pérennité de MFV, les facteurs facilitant la mobilisation des connaissances ainsi que les initiatives de formation continue. La CdP a permis de renforcer les réseaux de partenariat entre les chercheurs et les animateurs du programme MVF, ce qui pourrait avoir un impact important sur l’équité en santé chez les personnes âgées francophones vivant en situation minoritaire au Canada. Abstract Marche vers le Futur (MVF) is a telehealth program that has demonstrated a positive impact on the access to fall prevention services in Canada and the wellness of older Francophone adults living in minority situations. This project aimed to develop and implement a community of practice (CoP) to facilitate partnership and knowledge-sharing between MVF program facilitators across francophone communities in Canada. The creation of this CoP enabled twenty-two facilitators from five provinces to share strategies for recruiting, promoting, and sustaining the program as well as continuing to raise awareness around the importance of health prevention services tailored for older Francophone adults in Canada. Four virtual meetings were held to identify sustainability barriers, knowledge mobilisation facilitators, and continuing education initiatives. The CoP allowed to strengthen the partnership between researchers and program facilitators across diverse provinces which could impact health equity among older Francophone adults living in minority communities in Canada.

Reach, adoption, and implementation strategies of a telehealth falls prevention program: perspectives from francophone communities across Canada - O’Neil, Jennifer; Dionne, Nathalie; Marchand, Sylvie; Cardinal, Dominique; Handrigan, Grant; Savard, Jacinthe (Health Promotion and Practice, 2024)
Introduction. A fall may impact a person’s physical, emotional, and psychological well-being. Fall prevention programs are being implemented to reduce these negative outcomes. However, linguistic barriers in health services may reduce access to such prevention programs. A telehealth fall prevention program was designed to increase access to such programs in French for Francophone minority communities in Canada. This capacity-building project aimed to support community partners to deliver this telehealth program and document strategies used to reach, adopt, and implement the program within various Francophone and Acadian Minority Communities. Methods. A sequential explanatory mixed methodology was used to document reach, adoption, and implementation strategies and describe the lived experiences of program facilitators and organization representatives. Reach, adoption, and implementation were documented and analyzed descriptively, while lived experiences were analyzed using content analysis following the Consortium Framework for Implementation Research. Results. Twelve organization representatives or program facilitators from eight organizations operating in four different provinces participated in the study. Three themes emerged from the qualitative data on reach and adoption: external context, internal context, and capacity building. Four themes were identified as barriers and facilitators to implementation: level of preparation and time management, interpersonal relations and telepresence, exercise facilitation and safety, and technological problem-solving. Conclusion. Using tailored reach and adoption strategies such as prioritizing provinces with higher proportions of needs and training local community program facilitators may lead to the successful implementation of a new telehealth fall prevention program. Results from this study could potentially inform other primary prevention programs or telehealth program implementation.

Access to a telehealth falls prevention program: Mixed-method analysis from a health equity perspective - O’Neil, Jennifer; Dionne, Nathalie; Sauve-Schenk, Katrine; Savard, Jacinthe (Journal of Telemedicine and Telecare, 2026)
Introduction Access to falls prevention programs, addressing an important public health concern, is often limited for Francophone and Acadian minority communities. Technology has been used to deliver falls prevention programs, but health equity factors linked to improving its access for all are still poorly understood. This study aimed to document health equity factors influencing access from the perspective of older francophone adults in various communities across Canada. Methods Guided by the digital health equity framework, we used a sequential explanatory mixed method, including a descriptive sociodemographic questionnaire and semi-structured interviews, to document perspectives on access of persons who had completed different versions of a telehealth falls prevention program. Results Sixty-one participants from five provinces completed the sociodemographic questionnaire, of which most participants (n= 45) represented perspectives from francophone communities living in a minority situation. Results revealed that 91% of participants had access to a computer or tablet with adequate audio-visual components for telehealth. Twenty of these participants, from four provinces, shared their perspectives. The majority of them reported that falls prevention programs should be offered in their preferred language and with different delivery options that consider the social and safety preferences of participants. Eight recommendations informing policy and implementation emerged. Discussion Advocacy around digital connectivity is essential to ensure that all Canadians have equitable access to high-speed internet connections and proper infrastructure. Participants also raised the importance of adapting services to their linguistic realities, geographic location, safety, and basic needs to optimize the impact of the health services provided to them.

Évaluation de Marche vers le futur, un programme novateur de prévention des chutes offert par videoconference - Savard, Jacinthe; Labossière, Sophie; Cardinal, Dominique; Pinet, Bernard; Borris, Caroline (La Revue canadienne du vieillissement, 2018)
Several fall prevention programs have been implemented to reduce falls among seniors. In some rural areas or in French-speaking minority communities, the availability of such programs is limited. The objectives of this paper are to: (a) describe the Fall Prevention Program Marche vers le futur, offered in French, by videoconference; and (b) present the results of the evaluation of the program objectives. Results demonstrate that participants have improved their physical abilities, gained knowledge, adopted new behaviors and lifestyle habits. In short, Marche vers le futur reduces fall risk factors in a manner equal or superior to other programs. Marche vers le futur has made possible the provision of services in French in communities where availability of French-language resources is very limited, therefore fostering equity in access to health services.